Female Objects and Feminist Consciousness for the Purpose to Awake Readers’ Awareness: A Comparative Analysis between Angela Carter’s The Bloody Chamber and Anne Sexton’s Transformations - Liu Fenglin (Ital Publication, 2020)
The female object, as a symbolic image created by male authors to reduce the threat brought by females towards patriarchy, has become a method to express male sexual and domestic fantasies. However, in the fairy tale adaptation by two mid-twentieth century female authors-Angela Carter and Anne Sexton, the female object is used to evoke feminist consciousness. Although former studies have covered some feminism issues, for instance, the feminist awareness through the mirror image in Angela Carter’s The Bloody Chamber, and the direct metaphors such as “doll” and “soap pop” which lead to female objectification in Anne Sexton’s Transformations, little research has compared the distinctive psychological impacts that the narrative forms between the two mentioned texts have on readers. In the first section of this paper, how both authors deconstruct the female stereotypes and how they reinterpret modes of female agency in the original Grimm’s fairy tales have been examined. Based on the writers’ perspective, the first section would also explore the expression of female objects in their works. As for the second section, I would mainly focus on the psychoanalysis of Lacan’s mirror stages, and yet cover the awakening processes presented in the mirror images and symbols composed in the two adaptations. In the third section, the different narrative strategies utilized by Carter and Sexton in order to stimulate readers’ responses towards feminist consciousness would be illustrated.